CHARACTER EDUCATION IN EARLY CHILDHOOD - Yuniarni, Desni (Universitas Tanjungpura, 2012)
Childrens good characters should be formed since their early time growing up because it is an individuals set of psychological characteristics that influence persons ability and inclination for function morally, as Marvin Berkowitz said (William Damond, 2002). Besides, Dimermen (2009:9), educational prationers identified 10 characters which have to be developed in children such as: 1) respect, 2) responsibility, 3) honesty, 4) empathy, 5) fairness, 6) initiative, 7) courage, 8) perseverance, 9) optimism, 10) integrity. These characters can be transferred by school as an agent of education, called character education. Megawangi (2004: 95) said that character education is a way to educate children in order to decide wise decision and practice it in regular life, so they can give positive contribution for environment. Moreover, character education is an education to develop good character from children, make them able to judge which one right or wrong, care deeply about the right and then doing what they believe to be right. Shortly, character education can be internalized habituation about what is right, so that student become understand (cognitive) about what is right and what is wrong, and can feel (affective) the values of good thing and always trying to do that (psychomotor). Character education has to consist moral knowledge, moral feeling, and moral action. It is related to the habit, so it has to be practiced all the time. Moreover, build the good character needs communities character including family, school, religious institution, information media, government, and all supported component close to the young generation. The roles of school in this case are stated in learning process, habituation, extracurricular, and socialize. To develop character from children, school should not create a new curriculum but must integrate all national system which has been strong basic in formal education world. That is the implication of the character education. Last but not least, the best way in forming good character for children is through the model. Teacher here is the main component who plays important role in giving kinds of good examples, even by interaction with the student, routine activities, or spontaneous and incidental activities in the school. From those points above we hope that our young generation has much capability not only in cognitive side, but also in their attitude, manner, and their personality. KEYWORDS: character, education, early childhood